Spontaneous ventilation in the prone decube in patients with SARS Cov-2 infection without invasive mechanical ventilation - Uriol-Mantilla, Claudia Lizeth (2021)
Introduction. The severe acute respiratory syndrome type 2 coronavirus infection (SARS-CoV-2) that causes coronavirus disease 2019 (COVID-19) has significantly transformed the way hospital medicine is practiced in these last 4 months. Currently, there are a large number of patients who are admitted to health facilities by emergency presenting respiratory failure that rapidly evolves to the critical state of the disease, requiring in some cases admission to the intensive care unit (ICU) and the provision of ventilation invasive mechanics (IMV). Different strategies and methods have been carried out for the management of patients with SARS CoV 2 infection, one of them and with greater relevance is the prone position (PD), used to improve oxygenation levels in patients with syndrome of acute respiratory distress (ARDS). The PD position improves oxygenation levels, decreasing the gravitational gradient of pleural pressure, improving perfusion and ventilation of the lung parenchyma, increasing functional residual capacity and optimizing the ventilation / perfusion (V / Q) ratio of the injured lungs. Several studies show the great benefit of the PD position in patients with SARS CoV 2 infection; Therefore, it is currently being used as a non-invasive treatment to prevent deterioration of ventilatory function with subsequent intubation and admission to the ICU.